The relationship between emotions and confidence among wrestling athletes in Greece - Barbas, I.; Kouli, O.; Bebetsos, E.; Mirzaei, B.; Curby, D. G. (International Journal of Wrestling Science, 2011)
Understanding the role of emotions is critical if we are to explain, control and predict athletic performance. The Individual Zones of Optimal Functioning (IZOF) model attempts to describe and explain emotions related to an individual.s successful and poor performances (Hanin, 1997, 2000). The participants were 300 male wrestling athletes (160 greco-roman wrestlers and 140 freestyle wrestlers). Their ages ranged from 18 to 30 years (M=24.30, SD=3.70). All athletes completed the questionnaire on emotions (IZOF, Hanin, 2000), which was translated into Greek (Hanin, Papaioannou & Lukkarila, 2001). The aim of the study was the examination of a possible relationship between emotions and confidence in greco-roman and freestyle wrestlers in Greece. The results supported the psychometric properties of the assessment tool. Additionally, the results indicated statistically significant correlations, but no statistical significant differences in emotion categories of the questionnaire and confidence, between greco-roman and freestyle wrestlers. According to previous research, it is also important to indicate that emotional content and intensity are different in practice and competitions, and that they vary across pre-, mid-, and post-event performance situations (Hanin & Stabulova, 2002). Possible future research might replicate and extend the study.s findings, exploring an athlete.s anxiety, goal-orientations, motivation and performance, and developing effective intervention strategies.